PENGARUH NILAI TUKAR DAN INFLASI TERHADAP EKSPOR KOMODITAS BUAH-BUAHAN DI INDONESIA - Rieska Maghfirah; Fanny Nailufar (Jurnal Ekonomi Pertanian Unimal, 2024)
This research analyzes the influence of exchange rates and inflation on fruit commodity exports in Indonesia. The study utilizes a time series dataset spanning 24 years (1999-2022) from FAO (Food and Agriculture Organization), World Bank, and BPS publications. The analysis employs the ARDL (Autoregressive Distributed Lag) dynamic model using Eviews 10. The short-term results indicate that the exchange rate has a positive and insignificant effect on fruit commodity exports in Indonesia. In contrast, in the long term, the exchange rate shows a negative and negligible impact on these exports. Regarding inflation, the variable demonstrates a negative and significant effect on fruit commodity exports in the short term, while in the long term, inflation's impact is negative but insignificant.